Review of current trends for metal-based sandwich panel: Failure mechanisms and their contribution factors. (May 2021) - Faidzi, M.K.; Abdullah, S.; Abdullah, M.F.; Azman, A.H.; Hui, D.; Singh, S.S.K.
Graphical abstract: Highlights: Core design plays an important role in determining the performance of sandwich panel. Loss in density for core structure; lead to catastrophic failure on sandwich panel. Delamination are contributed by bonding interaction effect between the surface layer. Potential of magnesium alloy as main core material for sandwich panel. Bonding timing process has significant affect for interfacial bonding of sandwich panel. Abstract: This review outlines the evolution of sandwich panels based on recent work and older sources, focusing on the trends concerning sandwich panel achievements and applications, core materials, core designs, types of failure mechanism and factors which contribute to the failure of sandwich panel. The review begins with an extensive discussion highlighting the achievements and trends relating to sandwich panels over the past 50 years, including the most recent work published. The purpose of this paper is to re-evaluate the current core design of metal-based sandwich panels, and further elucidate on core design, core materials and the types of failure mechanism which sandwich panels usually experience under certain conditions. The main factors that contribute to the failure phenomena experienced by sandwich panels, such as geometries of core design, different configuration of core design, the adhesive interaction effect between the bonding layers of sandwich panels and the effect of sandwich panels under high-speed impact and blast loading are considered. Future issues regarding metal-based sandwich panel, including the use of new materials for the core, new concepts in core design and the possibility to extend sandwich panel use for heavier applications, such as the defence industry, are highlighted and discussed. At the end of this review, the authors draw attention to other researchers by suggesting a list of topic areas that need to be addressed by research in the near future.